Upaya Mendorong UKM Desa Pattalassang Melalui Penciptaan Nilai Tambah Singkong: Penelitian - Muh. Ma'ruf Idris; Herman Sjahruddin; Jamaluddin Jamaluddin; Andi Basrul; M.Syawal; Ardiansyah Halim; Usman Wahyuddin; Nurfadhli Wahid; Hasriana Hasnur; Nurhikma Nurhikma; Charly R Adug; Andi Tereza Harijanto; Fadila Arista Rahmat; Muhammad Ramlan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The villagers have been selling their cassava to traditional markets, while the demand for cassava is limited. As a result, a lot of cassava couldn't be sold in the market, so strong efforts from all village elements are needed to create added value for the cassava. This condition is the reason for the community service activities carried out for approximately 30 days, which were done by increasing the added value of cassava through processing it into chips, so that cassava that is not absorbed by the market can be processed in such a way as to increase residents' income. The methods used in this service began with observation and interviews, followed by socialization and training for the village residents. This community service activity is oriented towards empowering and increasing the income of village residents by transforming knowledge and skills through processing cassava into chips. This community service was carried out jointly by lecturers and students as the service group, along with the village's UKM in Pattalassang. The cassava value addition implemented has proven to increase the income of village residents, making it important to enhance it now and in the future.